Pretreatment neutrophil-to-lymphocyte ratio as a marker of outcomes in nivolumab-treated patients with advanced non-small-cell lung cancer. (April 2017) - Bagley, Stephen J.; Kothari, Shawn; Aggarwal, Charu; Bauml, Joshua M.; Alley, Evan W.; Evans, Tracey L.; Kosteva, John A.; Ciunci, Christine A.; Gabriel, Peter E.; Thompson, Jeffrey C.; Stonehouse-Lee, Susan; Sherry, Victoria E.; et al.
Highlights: NLR ≥ 5 is associated with inferior OS in nivolumab-treated patients with NSCLC. It is unclear whether this marker is predictive or prognostic in this setting. Additional studies are needed to validate the NLR as a marker of nivolumab outcomes. ECOG PS ≥ 2 and liver metastases were also associated with inferior OS. Abstract: Objectives: Efficient use of nivolumab in non-small-cell lung cancer (NSCLC) has been limited by the lack of a definitive predictive biomarker. In patients with metastatic melanoma treated with ipilimumab, a pretreatment neutrophil-to-lymphocyte ratio (NLR) < 5 has been associated with improved survival. This retrospective cohort study aimed to determine whether the pretreatment NLR was associated with outcomes in NSCLC patients treated with nivolumab. Methods: We reviewed the medical records of all patients with previously treated advanced NSCLC who received nivolumab between March 2015 and March 2016 outside of a clinical trial at the University of Pennsylvania. Patients were dichotomized according to pretreatment NLR < 5 vs. ≥5. Multivariable logistic regression and Cox proportional hazards models were used to assess the impact of pretreatment NLR on overall survival (OS), progression-free survival (PFS), and overall response rate (ORR). Results: 175 patients were treated. Median age was 68 (range, 33–88); 54% were female. Twenty-five percent of patients had an Eastern Cooperative Oncology Group Performance Status (ECOG PS) ≥2; 46% had received ≥2 prior systemic therapies. In multivariate analyses, pretreatment neutrophil-to-lymphocyte ratio (NLR) ≥5 was independently associated with inferior OS (median 5.5 vs. 8.4 months; HR 2.07, 95% CI 1.3–3.3; p = 0.002) and inferior PFS (median 1.9 vs. 2.8 months; HR 1.43, 95% CI 1.02–2.0; p = 0.04). Conclusions: In a cohort of patients with NSCLC treated with nivolumab in routine practice, pretreatment NLR ≥ 5 was associated with inferior outcomes. It is unclear whether this marker is predictive or prognostic. Prospective studies are warranted to determine the utility of NLR in the context of other biomarkers of programmed death-1 (PD-1) therapy.